FAKTOR-FAKTOR YANG MEMPENGARUHI LABA BERSIH PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI - Fandi Nur Mandela; Arif Nugroho Rachman (Bajang Institute, 2023)
The purpose of this study to find the variables that affect the net profit of pharmaceutical companies listed on the Indonesian stock exchange. This kind of research is categorized as quantitative research. Pharmaceutica companies listed on the Indonesian stock exchange between 2016-2020 which constitute the population. Retrieval of research data using an purposeful sampling approach, and collected as many as 35 samples from 11 companies and as many as 7 sample companies. for this reseach, multiple linear regression analysis is the method of analysis. The result is that operating income has a relevant impact on net income. the cash turnover ratio, inventory turnover ratio, and receivables turnover ratio all had no effect on net income. According to the simultaneous test of operating revenues, cash turnover, inventory and receivables have a large effect on net income.